2006
DOI: 10.1021/ja0576738
|View full text |Cite
|
Sign up to set email alerts
|

Photoreversible DNA Condensation Using Light-Responsive Surfactants

Abstract: A means to control DNA compaction with light illumination has been developed using the interaction of DNA with a photoresponsive cationic surfactant. The surfactant undergoes a reversible photoisomerization upon exposure to visible (trans isomer, more hydrophobic) or UV (cis isomer, more hydrophilic) light. As a result, surfactant binding to DNA and the resulting DNA condensation can be tuned with light. Dynamic light scattering (DLS) measurements were used to follow lambda-DNA compaction from the elongated-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 66 publications
4
144
0
3
Order By: Relevance
“…That is, the presence of bromide ions affects the PVA structure by decreasing its crystallinity due to the ability of NaBr as a hydrogen bond breaker [26]; consequently, it can be suggested that in more amorphous gels, due to the higher mobility of the PVA chains between the crystalline parts, DNA molecules evidenced stronger self interactions, generating aggregate structures and, thus, increasing the retention (α) of DNA inside the gel membrane. On the other hand, the effect of NaBr, on the DNA structure, in the gel membrane, is similar to that found by the addition of an azobenzene trimethylammonium bromide surfactant in DNA aqueous solution upon exposure to visible radiation [27]. Using the same arguments, the decrease in the rate constant of the DNA release with an increase of the retention degree can be attributed to a stabilization of DNA in the gel state.…”
Section: Mathematical Modelsupporting
confidence: 75%
“…That is, the presence of bromide ions affects the PVA structure by decreasing its crystallinity due to the ability of NaBr as a hydrogen bond breaker [26]; consequently, it can be suggested that in more amorphous gels, due to the higher mobility of the PVA chains between the crystalline parts, DNA molecules evidenced stronger self interactions, generating aggregate structures and, thus, increasing the retention (α) of DNA inside the gel membrane. On the other hand, the effect of NaBr, on the DNA structure, in the gel membrane, is similar to that found by the addition of an azobenzene trimethylammonium bromide surfactant in DNA aqueous solution upon exposure to visible radiation [27]. Using the same arguments, the decrease in the rate constant of the DNA release with an increase of the retention degree can be attributed to a stabilization of DNA in the gel state.…”
Section: Mathematical Modelsupporting
confidence: 75%
“…An increase in the CMC was accompanied by trans – cis photoisomerization, which was attributed to the increased polarity and altered molecular geometry of the cis isomer relative to the more hydrophobic and planar trans isomer (Table 1). 20 However, in some cases the magnitude of this change was significant, in particular that of AzoGlcNAc incorporating an N -acetyl glucosamine head group. In contrast, virtually no difference in the CMC was observed between the trans (0.33 mM) and cis (0.34 mM) dominated PSS of AzoXyl , further highlighting the effect of subtle head group configuration and polarity on the interfacial activity of this class of photosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the other external stimuli to trigger DNA decompaction and release, light input is considered to be advantageous benefitting from its capability of remote control [40][41][42]. For example, Lee developed a means to control DNA compaction and gene delivery by light input in cationic or cationic-anionic surfactant system [43,44]. Andreasson and coworkers described the photo-switched DNA-binding of a spiropyran amphiphile [45].…”
Section: Introductionmentioning
confidence: 99%